Workers, Managers, Productivity Kaizen in Developing Countries - Hosono, Akio; Page, John; Shimada, Go (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2020)
This open access book provides a glimpse into the Japanese management technique known as "Kaizen," and the ways it has been disseminated around the developing world. The novelty of this book is three-fold: it provides a contextualized view of the mechanisms of initiatives implementing Kaizen in developing countries; compared with productivity studies, it places the relationship between workers and managers at the center of inquiry, reflecting the intent of SDG8 concerning decent work and economic growth; and it provides an overview of the heterogeneity of Kaizen in terms of geography and firm size. This book explores how improving management techniques can support firms' productivity and quality. Given its wide range of case studies from across Africa, Asia and Latin America, this book will be of value to scholars, policymakers and advocates of sustainable development alike. Akio Hosono is senior research adviserto the JICA Research Institute. Holding a doctorate in economics from the University of Tokyo, he has held a variety of academic　posts, including a period as Director of the JICA Research Institute from 2011 to 2013. John Page is a Senior Fellow in the Global Economy and Development Program at the Brookings Institution in Washington, DC and has held positions at Princeton University, USA, the World Bank, Oxford University, UK, and the National Graduate Institute for Policy Studies, Tokyo, Japan. Go Shimada is an Associate Professor of Meiji University and a visiting scholar at the JICA Research Institute. He holds a PhD from Waseda University.